Sistema de monitoramento de dados para usinas fotovoltaicas - Gomes, Andreas Anael Pereira (2020)
The aim of the project is to implement a monitoring system for the photovoltaic plants installed on several campuses of the Federal University of Technology - Paran‡ (UTFPR) by their Solar Energy Lab (LABENS). The data is acquired by inverters connected by an RS-485 network to an embedded computer. The embedded computer is connected to the internet, transmitting the processed data to a server located in Curitiba. The data from the Curitiba server is then made available to the people involved in the project to be able to monitor the stations.